Unlocking the Potential of Migrants in Germany - Bergseng, Benedicte [Verfasser]; Degler, Eva [Verfasser]; Lüthi, Samuel [Verfasser] (OECD Publishing, 2019)
"The German vocational education and training (VET) system is admired around the world for its ability to prepare young people for skilled employment. In Germany, VET smooths transitions into work and is closely aligned with labour market demand. This report focuses on an unprecedented test of the German VET system: how to respond to the significant increase in migrants who arrived in the country in 2015-16. The study explores both the opportunities and the challenges presented by migration. Germany has already devoted significant attention to VET as a mechanism for enabling integration - and for good reason. Work-based learning assists integration because it demonstrably gives learners skills that employers want in real-world settings. The report assesses the barriers faced by learners in their journeys into and through VET, exploring how such challenges can be addressed. In addition, the study looks at system-wide issues in relation to how VET provision and integration policy is governed. Lastly, it explores opportunities for increased flexibility in the German VET system of relevance to all youth at risk of not succeeding in VET. In responding to migrant needs, German VET can become more inclusive without reducing quality." (Editor; BIBB-Doku)

Die Studie untersucht, wie Berufsbildungssysteme am besten auf etwaige Chancen und Herausforderungen der Zuwanderung reagieren können. Der Schwerpunkt liegt auf Deutschland und widmet sich der Frage, wie Deutschland mit den 1,5 Millionen Geflüchteten umgeht, die 2015/2016 in das Land kamen. Die Hindernisse, die diese überwinden müssen, sind hoch: Ihre Vertrautheit mit der beruflichen Bildung oder ihr Interesse daran sind oft begrenzt; Fähigkeiten und Fertigkeiten, die sie für Ausbildungsaufnahme und -erfolg benötigen, insbesondere Sprachkenntnisse, sind oft unzureichend. Die Studie befasst sich mit den Hindernissen, vor denen Bildungswillige auf ihrem Weg in und durch die Ausbildung stehen, und mit möglichen Lösungswegen. Der Schwerpunkt liegt auf Geflüchteten, die im Alter zwischen 16 und 35 Jahren und in ihrem ersten Ausbildungsjahr sind, wobei die Erkenntnisse in Bezug auf die gesamte Gruppe der Migranten dargestellt werden. (BIBB-Doku)
Keywords: P 1.5 Migranten; G 1.3.2.1 Zugänge; Flüchtling; Migrant; Berufliche Integration; Berufsausbildung; Berufsvorbereitung; Berufsbildungssystem; Berufsbildungspolitik